2015
DOI: 10.5771/0935-9915-2015-3-227
|View full text |Cite
|
Sign up to set email alerts
|

Working time arrangements and family time of fathers: How work organization(s) shape fathers’ opportunities to engage in childcare

Abstract: Working time arrangements and family time of fathers:How work organization(s) shape fathers' opportunities to engage in childcare ** This analysis takes the diagnosis of a gap between German fathers' attitudes and practices as starting point to analyze the influence of the work organization on a father's time with his children. With qualitative interview data and quantitative diary data, the fathers´ ideals and their practices are confronted systematically. It is found that fa-thers´ work time arrangements may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 16 publications
0
15
0
1
Order By: Relevance
“…Hildebrandt, 2006;Hill et al, 2010), parenting time (e.g. Reimer, 2015) and wages (e.g. Fang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Hildebrandt, 2006;Hill et al, 2010), parenting time (e.g. Reimer, 2015) and wages (e.g. Fang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, contemporary changes of fatherhood often are characterized as showing a gap between fathers' (more modern and egalitarian) attitudes and (more traditional and inequal) practices (Bergmann and Hobson 2002;Bühlmann, Elcheroth, and Tettamanti 2010;Cyprian 2005;Grunow 2007;LaRossa 2012;Meuser 2009). The reasons for this gap are mostly seen as originating in constraints for fathers caused by mothers' gatekeeping (e.g., Gaunt 2007;Kulik and Sadeh 2014), by structural and cultural factors at their workplace (e.g., Bygren and Duvander 2006;Haas, Allard, and Hwang 2002;Hallberg and Klevmarken 2003;Reimer 2015), or by economic considerations at the level of the family (e.g., Geisler and Kreyenfeld 2011) and the level of policies (Gornick and Meyers 2003) that codify the fathers' role as the main breadwinner. The explanation of changes in fatherhood still is a contested question which might in part, however, stem from ambiguity in different measures of paternal engagement (e.g., Lamb 1987).…”
Section: Changing Fatherhoodmentioning
confidence: 99%
“…In this regard, Seward et al (2006) show that especially employers’ tendency to equate working late with employees’ commitment makes them stay longer at work. Regarding the influence of fathers’ workplace, it was also found that job security and job flexibility are relevant for fathers’ time with children (e.g., Craig and Mullan 2011) as well as the possibility to use flexible work arrangements like flextime or working from home (Reimer 2015).…”
Section: Literature Review: Determinants Of Factors For Fathers’ Takementioning
confidence: 99%
“…Particularly mothers' employment participation and fathers' workplaces (e.g. Fagan & Norman, 2016;Haas & Hwang, 2008;Hallberg & Klevmarken, 2003;Kitterød & Pettersen, 2006;Reimer, 2015Reimer, , 2019Smith Koslowski, 2008) are of particular relevance in explaining fathers' engagement in childcare outside of leave. Thus, besides "father-sensitive" parental leave policies (O'Brien, 2009), the mother's equal employment participation, greater equality in pay for women and father-sensitive workplace cultures may be important facilitators for a move towards gender equality in care.…”
Section: Discussionmentioning
confidence: 99%